Right atrial perforation after an endocardial screw-in atrial lead implantation - Ahmet Avcı; Kenan Demir; Bülent Behlül Altunkeser (KARE Publishing, 2013)
A 24-year-old female underwent implantation of a right-sided dual chamber permanent pacemaker for cardioinhibitory syncope with active fixation atrial lead. Five days after the procedure, the patient developed pleuritic chest pain and difficulty in breathing. Minimal pericardial effusion and right hemopneumothorax were found. The atrial active screw-in lead was visualized just above the right atrial appendage with its helix perforating the right atrial wall, pericardium and pleura, reaching the right mid-lobe. Lead extraction was performed, and a passive bipolar atrial lead was implanted during the same session without any problems.